The Political Liability procedure against Carlos Muñoz Roca-Tallada, count of la Viñaza. A revolutionary aristocracy member? - González Gil, Ana (Huarte de San Juan. Geografía e Historia, 2019)
This article discusses one of the procedures carried out by the Court of Political Liabilities of Navarra, in order to punish personal political activities against the «National Movement». The peculiarity of this procedure lies in the singular personality of the accused, an aristocracy member and, at least in a moment of his life, a CNT union militant.